FOOD SAFETY CULTURE AND "BALI BELLY": A CASE STUDY IN LUXURY HOTEL - Bhupendra, Putu; Jayaditya, Made; Arya Armady Galung Saputra, Kadek; Widiantara, I Gusti Made Agung; Aji Kusuma Kepakisan, I Gede (JURNAL KEPARIWISATAAN, 2025)
This research investigates the rising incidence of "Bali Belly" (traveler's diarrhea) among Australian tourists in Bali, Indonesia, despite widespread awareness of common risk factors such as contaminated water, food, and ice. While existing literature primarily focuses on street food and lower-end establishments, this study examines the issue within a five-star luxury hotel in Ubud, Bali, revealing a concerning disconnect between perceived safety and actual hygiene practices. Through qualitative methods, including in-depth interviews and participant observation, the research uncovers hidden hazards, including contaminated seafood and compromised sanitation within the hotel's food and beverage operations. The study highlights a pervasive "culture of hygiene" that transcends establishment type, suggesting that systemic issues, including long working hours, pressure to prioritize guest satisfaction over employee well-being, and inadequate incident reporting, contribute to the persistence of foodborne illness risks. The findings emphasize the need for a multi-faceted approach to address "Bali Belly," moving beyond surface-level precautions to tackle deeply ingrained cultural and operational challenges within Bali's hospitality sector.